1997
DOI: 10.1007/bf01367660
|View full text |Cite
|
Sign up to set email alerts
|

Cell cultures and nephrolithiasis

Abstract: While the physical chemistry of stone formation has been intensively studied during the last decade, it has become clear that the pathophysiology of renal stone disease cannot be explained by crystallization processes only. In recent years, evidence has emerged that the cells lining the renal tubules can have an active role in creating the conditions under which stones may develop. Since it is difficult to study these mechanisms in vivo, cultured renal tubular cells have become increasingly popular for the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…Urinary macromolecules, e.g. glycoproteins, proteins and glycosaminoglycans, adherent or bound to the crystals, counteract both crystal aggregation and crystal growth [12,20], and macromolecules are also important for the adherence of crystals to the tubular cells and for crystal-cell interaction [21,22].…”
Section: Epidemiological Considerationsmentioning
confidence: 99%
“…Urinary macromolecules, e.g. glycoproteins, proteins and glycosaminoglycans, adherent or bound to the crystals, counteract both crystal aggregation and crystal growth [12,20], and macromolecules are also important for the adherence of crystals to the tubular cells and for crystal-cell interaction [21,22].…”
Section: Epidemiological Considerationsmentioning
confidence: 99%
“…Several groups of investigators have suggested that an important early event in the formation of kidney stones is the attachment of calcium oxalate (CaOx) crystals to the apical surface of renal tubular epithelium (1)(2)(3). Well-polarized, undisturbed tubular epithelial cells in culture demonstrate little capacity for crystal attachment (4 -6).…”
mentioning
confidence: 99%
“…It has been reported that crystals interacting with the tubular epithelium lead to a retention and accumulation of crystalline material in the kidney and eventually to the development of a renal stone [20]. The mechanism is difficult to study in human subjects but is supported by several reports from cell cultures [21]. The most frequently associated phenomenon is tubular cell injury from high oxalate load in cell culture.…”
Section: Discussionmentioning
confidence: 79%